The bills of the parish church in Zator from the years 1559 to 1561 - Przemysław Stanko (Folia Historica Cracoviensia, 2012)
The bills of the parish church in Zator from the years 1559 to 1561 presented in this article complete the current knowledge about the history of the parish in Zator in the beginning of the modern age. They include information about running renovations and repairs as well as they bring in a lot of interesting information about the parish school. They provide intelligence on the care over church paraments and the ways of obtaining them. They also bring unknown so far, especially for the linguists, knowledge about bring the knowledge of the surnames of both Zator townspeople and peasants living around the city, which might be of particular interest for linguists.